(untitled) (LACCEI, 2024)
Industry 4.0 is a strategic tool that allows the integration of processes and areas in an organization through two basic pillars: automation and digitization, turning this into a competitive advantage of interest for small and medium-sized companies in the manufacturing sector in Latin America that have as one of their purposes to be visionary companies. The objective of the study was to identify the critical success factors required to implement Industry 4.0 in pymes in the manufacturing sector in Latin America, by conducting a systematic review. The main results were the identification of the similarities and differences of the critical success factors for the implementation of Industry 4.0 in pymes in the manufacturing sector in Ecuador, Argentina and Peru. Having as conclusions that the critical success factor in common among pymes in the manufacturing sector of the countries of Ecuador and Argentina to implement Industry 4.0 is the technological factor, while for the countries of Ecuador and Peru it is the strategic factor, and for the countries of Peru and Argentina it is the digital factor. Finally, it was concluded that pymes in the manufacturing sector in Ecuador differ from those in the countries of Argentina and Peru in the analysis of their critical success factors for implementing Industry 4.0 through a maturity level under the use of a Likert scale.